Invaluable and outsourced: experiences of private company cleaners working in the public hospital sector in Cape Town - Petro, Lyndsey (Department of Sociology, 2014)
In the hospital context, and in research on hospitals, cleaning staff often find themselves on the periphery. This peripheral status is exacerbated when cleaners are employed by private cleaning companies. The intersection of locations these cleaners find themselves in, as cleaners, outsourced support staff and members of the working poor means that their work-life experiences take a particular shape. In an attempt to better understand the work experiences of these staff members, I conducted qualitative interviews with 8 female private company cleaners from four different public hospitals in Cape Town. Alienation, job insecurity, working poverty and emotional labour are used as tools to unpack and understand these experiences. Here I argue that these workers perform work that is far from ancillary or non-essential, work central to the functioning of the hospital space. However, the scope of their work is unappreciated and as a result, so too are the health and safety risks they are exposed to, making them especially vulnerable. This vulnerability is compounded by insecurity and the struggle to make ends meet. Alienating conditions are evident as they are constantly reminded of their status at the bottom of the hospital hierarchy and made to feel insignificant. Engaging with the experiences of these cleaners shows how alienation, insecurity, working poverty and emotional labour manifest in interesting ways. It allows us to see the numerous challenges they face in their working lives, particularly as private company cleaners in a hospital.